Поліпшення роботи кранових металевих конструкцій шляхом застосування гідроприводу та деяких інших рішень в механізмах пересування та повороту - Григоров, Отто Володимирович; Аніщенко, Галина Оттівна; Петренко, Надія Олександрівна; Стрижак, Всеволод Вікторович; Турчин, Ольга Володимирівна; Радченко, В. С.; Окунь, Антон Олександрович; Глушкова, М. Ю. (Одеський національний політехнічний університет, 2019)
Наведені результати досліджень на натурних кранах з гідродинамічними та гідростатичними приводами механізмів пересування та повороту – мостових, баштових та портальних. Дані рекомендації щодо суттєвого збільшення в гідроприводах граничної кількості втомних циклів в співвідношенні до приводу з фазним ротором. Наведені варіанти поліпшення точності виставлення ходових коліс за допомогою лазерної техніки. Рекомендовано впровадження підпружених ходових коліс, високоміцних болтів, електрозаклепок та сталей з високими границями текучості.

The results of investigations of dynamic loads on cranes with hydrodynamic and hydrostatic drives are given. The mechanisms of movement and slewing with these drives on bridge, tower and portal cranes are explored. The obtained results, which show that when applying the hydrodynamic drive, the stress decreases by 10%, for hydrostatic drive – by 40%. All tests were carried out in factory conditions on field cranes. In this case, comparative studies were carried out for bridge cranes with a load capacity of 15/3 tons, 20/5 tons, 30/5 tons, 6.3/5 tons, tower cranes with a carrying capacity of 9.3 tons, portal cranes with a carrying capacity of 10 tons. As a result of numerous internships in Germany and the study of technology of the aligning of running wheels and the designs of the bearing boxes itself, the technology of the aligning of running wheels of the firm Kötten by applying of laser technology is recommended. To reduce skewing forces that occur between the wheel and the crane rail, it is recommended to use springing wheels with synthetic rubber washers. Such a device proposed by the authors and tested in Kharkiv also significantly reduces the vertical loading of the wheels from the passing of crane rails. On the basis of the study of foreign investigations, the authors recommend: - the introduction in steel structures of new carbide- and nitrideforming iron alloys with values of yield stress of 4-5 times bigger than Steel СТ3 (for example, the steel Weldox 1100 or 1300 which has σ₀‚₂ = 1100 MPa and σ₀‚₂ = 1300 MPa respectively, which leads to a decrease thickness for sheets and, as a consequence, to increasing fatigue resistance); - applying of high-strength bolts and electric rivets for connection of main and end beams. This will prevent the fault of geometry from typical deformations.
Improvement of crane steel structures work the way of applying of hydraulic drive and some other solutions in mechanisms of movement and slewing
Keywords: пошкодження; навантаження; гідродинамічні приводи; гідростатичні приводи; вузли кранів; втома; осцилограми випробувань; damages; load on steel structures of cranes; hydrodynamic drives; hydrostatic drives; fatigue of crane units; oscillograms of tests